HDAC inhibition attenuates cardiac hypertrophy by acetylation and deacetylation of target genes - Ooi, Jenny Y Y; Tuano, Natasha K; Rafehi, Haloom; Gao, Xiao-Ming; Ziemann, Mark; Du, Xiao-Jun; El-Osta, Assam (Epigenetics, 2015)
Pharmacological histone deacetylase (HDAC) inhibitors attenuate pathological cardiac remodeling and hypertrophic gene expression; yet, the direct histone targets remain poorly characterized. Since the inhibition of HDAC activity is associated with suppressing hypertrophy, we hypothesized histone acetylation would target genes implicated in cardiac remodeling. Trichostatin A (TSA) regulates cardiac gene expression and attenuates transverse aortic constriction (TAC) induced hypertrophy. We used chromatin immunoprecipitation (ChIP) coupled with massive parallel sequencing (ChIP-seq) to map, for the first time, genome-wide histone acetylation changes in a preclinical model of pathological cardiac hypertrophy and attenuation of pathogenesis with TSA. Pressure overload-induced cardiac hypertrophy was associated with histone acetylation of genes implicated in cardiac contraction, collagen deposition, inflammation, and extracellular matrix identified by ChIP-seq. Gene set enrichment analysis identified NF-kappa B (NF-κB) transcription factor activation with load induced hypertrophy. Increased histone acetylation was observed on the promoters of NFκB target genes (Icam1, Vcam1, Il21r, Il6ra, Ticam2, Cxcl10) consistent with gene activation in the hypertrophied heart. Surprisingly, TSA attenuated pressure overload-induced cardiac hypertrophy and the suppression of NFκB target genes by broad histone deacetylation. Our results suggest a mechanism for cardioprotection subject to histone deacetylation as a previously unknown target, implicating the importance of inflammation by pharmacological HDAC inhibition. The results of this study provides a framework for HDAC inhibitor function in the heart and argues the long held views of acetylation is subject to more flexibility than previously thought.